Identifying the impact video and photo content posted on social media has on Gen Z users’ consumer behaviour. - Burgers, Jené (The IIE, 2022)
The aim of this research was to identify the impact video and photo content posted on social media has on Gen Z users’ consumer behaviour. Despite the focus of social media platforms shifting from photo to video content it was realised that there was limited research as to which format better met the marketing needs of Gen Z consumers in terms of capturing their attention and persuading a positive purchase decision. This became an area of interest as social media has become one of the most utilised methods for brands to communicate with consumers and understanding which types of content were most efficient could assist in reduce time and marketing costs. This research was conducted as a quantitative study and made use of an online curated questionnaire with a sample of n=43. Based on the sample brands may find it useful that although video content is more popularly consumed by Gen Z and is the more preferred method for receiving communications, however the elements that contribute to the effectiveness of the content are of potentially more importance that the content format itself, these specifics are in actual fact where the contents successful impact on consumer behaviour lies.
Keywords: Marketing; Brand communication; Digital brand communication; Consumer behaviour; Zoomers; Digital natives; Consumer attention; Purchase decision